PENGEMBANGAN MEDIA CHART PROPORSI TUBUH WANITA FASE E DI SMK NEGERI 8 SURABAYA - Natasha Kriswidowati Dwianggraeni; Inty Nahari (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Student learning outcomes are influenced by students' learning styles. The background of this research is based on previous studies which prove that students in the fashion design department tend to have a visual learning style. Video tutorial learning media had been previously applied, but this media was considered less than optimal in supporting the learning process. Video media conveys information at the same time, resulting in a lack of interaction in the classroom between teachers and students to discuss the material. Therefore, this study attempts to use chart media. The objectives of this study are to describe the feasibility level of the media, to describe student responses to the chart media, and to determine student learning outcomes. In this study, the type of research used was a One Shot Case Study. The feasibility level of the chart media based on assessments from three aspects media, material, and language showed results that were Highly Valid with a score of 3.58. The results of student response data to the chart media showed Very Good results with a score of 81.3%. The learning outcome data of Class X Fashion Design 2 students showed that 100% of students completed their learning.